Design em movimento: elementos da linguagem gráfica nos créditos de abertura de filmes - Taú, Marcio Rodriguez (2017)
This dissertation investigates the use of graphic elements in the cinema, with the purpose of understanding how the design can collaborate to the construction of the audiovisual message and to identify the potentialities that the movement can add to the graphic compositions in open titles film. The project started with the realization that more and more graphic designers have the need to incorporate time and movement into their multiplatform projects, which in turn raises a number of theoretical and practical reflections. Thus, within the delimited theoretical scope, subjects related to moving image, principles of animation, digital graphic design, motion graphics and the graphic design in the cinema and open titles films were approached through authors like Arlindo Machado ( (2005 and 2010), Gilles Deleuze (1985 and 1990), Paul Wells (1998 and 2008), Donis Dondis (2007), Ellen Lupton (2013 and 2015), Matt Woolman (2004), Lev Manovich 2007, 2008 and 2012) and Gemma Soloma and Antonio Boneu (2007), among others. Finally, as a case study, a brief contextualization is presented, followed by the analyzes of the opening credits of the films: “Até que a sorte nos separe 2” (2013, direction: Roberto Santucci) and “Meu passado me condena: o filme”(2013, directed by: Julia Rezende). The proposal to choose these films was to provide a look at the contemporary production of Brazilian audiovisual graphic design, as well as to enable a study on open titles national films - not identified in the literature of the area consulted in this research